Reconciliation of mass-asymmetry systematics for incomplete fusion. (March 2015) - Singh, Pushpendra P; Yadav, Abhishek; Sharma, Vijay R; Kumar, R; Sharma, Manoj K; Singh, B P; Singh, R P; Muralithar, S; Bhowmik, R K; Prasad, R
Abstract: The onset and strength of incomplete fusion (ICF) has been studied in the framework of Morgenstern's mass-asymmetry systematics. The fraction of ICF has been deduced in 12 C+ 169 Tm system at energies ranging from 1.02V b to 1.64V b (V b = 54.94 MeV from the analysis of excitation functions (EFs). It has been found that the ICF starts influencing complete fusion at noticeably lower, β-values (i.e., 0.025 or 2. 5% of c) than that proposed by Morgenstern (i.e., ≈ 6% of c). The fraction of ICF increases with entrance channel mass-asymmetry for individual projectiles, termed as projectile dependent mass-asymmetry (ProMass-) systematics. The proposed ProMass- systematics has withstood all tests that have been done for fairly large number of systems to verify its validness.